A framework of facilities management service user indicators through user experience to achieve service excellence in waste management services in Malaysian local governments - Umar, Mohammed Akilu (2018)
Service excellence is a new paradigm in Malaysian local governments that is responsible for waste management including cleaning and garbage collection as part of facilities management services. Urbanisation has created a quest for excellent services which is associated with change in consumption pattern and increase in waste generation in the country. The practice of Service quality has issues, especially in operationalisation. Service users are not satisfied with services on waste management services in the state of Johor. This necessitates empirical study aimed at proposing Framework of Facilities Management service user indicators to achieve service excellence in waste management services Malaysian in local governments. The methodology involved mixed method and data was collected from service users in five local governments which included Iskandar Puteri City Council, Pasir Gudang Municipal Council, Kulai Municipal Council, Pontian District Council and Johor Bahru City Council in Iskandar Malaysia. Twenty-five interviews were conducted and analysed using Nvivo version 8.0. One thousand seven hundred and fifty questionnaires were administered and SPSS version 23 was used for the analyses. Exploratory Factor Analysis was first conducted out of which seven components emerged; meeting user needs, service promise, dealing with complaints/problems, development & innovation, friendly and helpful service, measurement analysis, equipment & maintenance are used to run Logistic Regression and the result revealed that service users recognized meeting the needs of the service users and it is level of significance is 0.012, understand and correct problems is 0.000, performance measurement to deliver service promise is 0.002, knowledge friendly and helpful is 0.000 because they add more values to waste management services hence most significant indicators for values to be gained. While the result from Nvivo Analyses revealed that to achieve a good service user experience, the local governments needs to focus on the service users, utilise it is service experience and provide personal touch in service delivery, promise on delivery, understand service user needs, customer experience, deals with complaints, enhance it is operational process and measurement analysis. The overall result revealed that customer focus needs to be enhanced, adding personal touch, promise on delivery and dealing with problems and going extra mile on services. It is also discovered that service users preferred pleasant service delivery and handling customer complaints positively improve service user satisfaction. Future study should consider the service providers as the respondents and the study should also be replicated in other local governments. The study would benefit policy makers and local governments.